Efficiency of foliar dressing of winter wheat - Л. В. Худолій (Plant Varieties Studying and Protection)
Purpose. To elaborate winter wheat cultivation technologies based on balanced fertilizer system that combines application of mineral fertilizers and the increase of their efficiency by the use of preparations with microelements.